Morpho-Physiological Traits of Soybean as Affected by Drought (Bangladesh Agronomy Journal, 2020)
An experiment was conducted to study the effects of water deficit stress on morphophysiological parameters in soybean plant in pots at the Department of Agronomy, Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur, Bangladesh during February to June, 2018. Seven soybean genotypes namely,i) G00081 ii) G00056 iii) Shohag iv) G00078 v) G00137 vi) G00035 and vii) G00060 were grown in two watering regimes viz. control (80% of the field capacity) and water deficit stress (50% of the field capacity). Morpho-physiological traits including plant height, number of leaf, relative water content, water saturation deficit, chlorophyll, proline, dry matter and yield were investigated. Results indicated that genotypic variability was found in water deficit stress tolerance in soybean. It was found that leaf of the genotype G00081 maintained higher water content, higher accumulation of prolineas well as less reduction of chlorophyll compared to other genotypes studied. Total dry matter accumulation and grain yield plant-1was also higher in this genotype. Genotype G00081 also showed relatively higher water deficit stress tolerance. On the contrary, G00035 was found to be susceptible showing lower yield. Higher water deficit stress tolerance in G00081 was attributed to higher relative leaf water and chlorophylls with accumulation of higher amount of proline.Bangladesh Agron. J. 2019, 22(2): 41-54